An update on leprosy immunopathogenesis: systematic review - Silva, Marcos Jessé Abrahão; Silva, Caroliny Soares; Brasil, Thiago Pinto; Alves, Ana Karoliny; dos Santos, Everaldina Cordeiro; Frota, Cristiane Cunha; Lima, Karla Valéria Batista; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Immunology, 2024)
Leprosy is a chronic infectious condition and the main cause of neuropathy that occurs brought on by M. leprae. It is known that the biological characteristics of the human host, such as the immunological ones, have a higher influence on the pathology of this disease than the intrinsic mechanisms of the bacterium. The objective of this work was to review the scientific knowledge about the relationship between immunopathology and the severity of leprosy. A systematic review following the PRISMA 2020 recommendations was conducted in the PUBMED, LILACS, SciELO and Science Direct databases using articles in English, Portuguese or Spanish between January 2011 and May 2022 with the descriptors "Leprosy/Immunology", "Cytokines" and "Mycobacterium leprae". A methodological quality assessment was carried out using the JBI checklists. A total of 49 articles were included. There is a relationship of greater severity of infection associated with lower release of MHC molecules in response to PGL-1 that inhibit the promotion of resolving T lymphocytes arising from dendritic cells (DCs) stimulation. In addition, the differentiation of macrophage phenotypes dependent on the activation of PRRs can define activation and the distinct type of T helper (Th) cells involved according to severity. Activated CD8+ T cells also have distinct types at the appropriate poles of the disease, and B cells show at the most severe pole of the LL, specific induction of IgA and more Treg-type CD8+ T cells that further contribute to T cell anergy. Therefore, the adaptive immune system aggravates nerve damage and defines the type of leprosy, while the innate immune system is considerably more significant in the onset of nerve damage, symptomatic of the initial presentation of illness and in several critical immune responses, including inflammation and elimination of dead M. leprae.